A személyes szabadsághoz való jog érvényesülése a Bűnvádi Perrendtartásban - Szabó, Zsanett (Debreceni Jogi Műhely, 2014)
In this study, first of all I am dealing with the question, how the right to personal liberty prevails in the Bűnvádi Perrendtartás, however at the beginning I would like to introduce how the law for the personal liberty formed and how it appeared in Hungary and in the international documents, so in the British, American and French law as well.The most serious barrier of the personal liberty is the criminal law, so i find it especially important to examine that for this reason what kind of safeguards were placed into the Bűnvádi Perrendtartás.In general it can be said that the most important guarantees of the personal liberty are found in the principles of the criminal law, for example presumption of innocence, and through this it prevails in the Bűnvádi Perrendtartás' system.Firstable the limitation of the personal liberty has to be looked in the coercive measures, so I studied the pre-trial detention institution, that besides the basic principle what kind of safeguards were brought in by the legislature.In the end, it can be said that the right to personal liberty influences the whole Bűnvádi Perrendtartás, and in the cases where there were limitations, they always solved it with a safeguard.